The motion of gas bubbles in a liquid under the influence of acoustical standing wave - CZYŻ, H.; ŚCIUK, W. (Archives of Acoustics, 1997)
This paper comprise the results of theoretical analysis of the problem of the forces influencing the gas bubbles in a liquid in a stationary wave field. The problem of the motion of small particles suspended in the gaseous medium (aerosols and fumes) has been studied intensively starting from the forties of our century in connection with the technical application of the acoustic coagulation for the precipitation of gases. This paper considers the equation of the motion of a gas bubble in a standing wave field under the influence of the drift and the resistance forces in the Stokes and Oseen approximation. We take into account the drift related to the radiation pressure, periodic viscosity changes and the asymmetry of motion of gas bubble vibrating in a standing wave field. This study considers an estimation of the intensity of the drift forces of types R, L and A as a function of the bubble radius at 10–100 kHz frequency of the wave. We give the general properties of the solutions of the motion equation of the gas bubble in the case of large attenuation constants, corresponding for typical values of the drift forces.